2012
DOI: 10.1159/000337742
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Tumor Necrosis Factor-α Downregulate Antimicrobial Iron Transport Protein, Nramp1, in Chronic Hemodialysis Patients: A Key Factor for Infection Risk

Abstract: Background/Aims: The susceptibility of patients on maintenance hemodialysis (MHD) to infections is a major cause of mortality and morbidity. Natural resistance-associated macrophage protein 1 (Nramp1) regulates intracellular pathogen proliferation, and its mRNA expression is highest in polymorphonuclear leukocytes (PMNLs). The purpose of this study was to determine the level of Nramp1 in PMNLs from MHD patients and the factors affecting its expression. Methods: Twenty MHD patients and 24 healthy volunteers (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…On the other hand, tumour necrosis factor-a (TNF-a) signalling in the dopaminergic neurones is found to be elevated in PD [43,44]. It is noted that Nramp1 expression is reported to be up-regulated by IFN-c [45], while down-regulated by TNF-a [46]. Thus, the inverse patterns of Nramp1 expression in the neurone and microglia may be attributed to cell-dependent response to cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, tumour necrosis factor-a (TNF-a) signalling in the dopaminergic neurones is found to be elevated in PD [43,44]. It is noted that Nramp1 expression is reported to be up-regulated by IFN-c [45], while down-regulated by TNF-a [46]. Thus, the inverse patterns of Nramp1 expression in the neurone and microglia may be attributed to cell-dependent response to cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The bone marrow has a constant need for iron to produce erythrocytes and leucocytes (Jacobs & Summers, 1981; Fonseca et al 2003; Drakesmith & Prentice, 2012). The main regulator of iron stores throughout the body is hepcidin and hepcidin expression is increased in certain tissues, such as macrophages, during inflammation (Moriguchi et al 2012; Wang et al 2012; Wu et al 2012). Lactoferrin, lysozyme, and many other antimicrobials and anti-inflammatory molecules also work by modulating the gut microbiota, promoting growth of beneficial bacteria like Bifidobacterium and Lactobacillus (Hu et al 2012; Maga et al 2012), which in turn lower the pH of the gut and discourage the growth of pathogenic bacteria (Ljungh & Wadström, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that in dialysis patients without infection or malignancy, the iron level of PMNLs is increased and is associated with the downregulation of the iron export protein ferroportin (FPN) and upregulation of the iron import protein transferrin receptor (TfR). Additionally, the chemotactic peptide f-Met-Leu-Phe-stimulated degranulation activity of lactoferrin is also decreased [21,22] . Thus, human hosts with micro-inflammation, such as CKD patients, may use iron withholding as a form of nonspecific immunity to prevent infection in the presence of extracellular-residing microorganisms, even in the absence of infection.…”
Section: Host Factorsmentioning
confidence: 99%
“…M. tuberculosis growth and iron content were reduced in the macrophages from these patients compared with those from healthy adult volunteers [42] . As for the host defense, essential micronutrients, such as iron, are sequestered from intracellular M. tuberculosis by being exported from the phagosome by the divalent metal cation transporter natural resistance-associated macrophage protein 1 (Nramp1) [22,41,44] ( fig. 1 ).…”
Section: Host-pathogen Interactionsmentioning
confidence: 99%
See 1 more Smart Citation